Invisible learning and technologies. Realities and voices of basic education teachers during the COVID-19 pandemic (Technological Innovations Journal, 2022)
The goal of this research was to identify the way in which basic education teachers develop the process of appropriation of Information and Communication Technologies.   During the COVID-19 pandemic, the development of technological skills to face emerging educational challenges in the contemporary context becomes significant through the use of different resources and technological means. The research was done through the qualitative approach, in which 6 semi-structured interviews were carried out with teachers who had more than 20 years of experience in the educational service, the results indicated that they developed digital skills such as: information search, design of digital teaching materials and platform management, as well as socio-emotional abilities such as empathy, collaboration, critical thinking and complexity management.
Keywords: appropriation; teachers; education; technology; ICT